Uses and Appropriations of Greek Cynicism in Contemporary Counterculture - Notario Pacheco, Fernando (Gerión. Revista de Historia Antigua, 2019)
The relationship between the ancient intellectual traditions from the Classical world and modern culture has been a frequent topic of study by classical scholarship. Nevertheless, there are some philosophical schools that have received considerably less attention, as it may be the case of ancient Cynicism. On the other hand, the problem concerning the uses, abuses and cultural appropriation of the Classical world in contemporary times has received an unbalanced attention. This paper analyses the relationship between modern American counterculture, as it emerged during the 1960s, and ancient Cynicism through the figure of Diogenes of Sinope in the countercultural press. This analysis suggests a broader scope concerning the potentialities, limitations and contradictions of the complex dynamics between ancient Cynicism and modern counterculture.
Keywords: Cynicism; Counterculture; Hippie Movement; Classical Reception; Diogenes of Sinope